2016
DOI: 10.1525/nclr.2016.19.1.42
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Comprehensible Youth Interrogation Rights

Abstract: Although youth in many Western countries have been afforded enhanced legal protections when facing police interrogations, the effectiveness of these protections may be limited by youth’s inability to comprehend them. The ability to increase the comprehension of Canadian interrogation rights among youth through the simplification of waiver forms was assessed. High school students (N = 367) in grades 9, 10, and 11 were presented with one of three waiver forms that varied in level of complexity. Comprehension of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 20 publications
2
33
1
Order By: Relevance
“…The second key finding was that the vast majority of interrogators in our sample did not make use of multiple and varied methods to assess and aid understanding. Consistent with previous studies, the youth in this sample typically claimed to understand the rights with a "yes" answer, even though research has shown that youth tend to demonstrate a lack of understanding when explaining interrogation rights in their own words, have serious misconceptions about their interrogation rights, and simply cannot understand the complex information presented to them (e.g., Cooke & Philip, 1998;Fenner et al, 2002;Freedman et al, 2016;Shepherd et al, 1995); very rarely did interrogators in our sample attempt to verify the youth's understanding. With respect to seeking evidence of understanding, youth were asked to explain all four rights in their own words in less than 10% of interrogations, and youth were asked to explain at least one of the rights in their own words in just over a third of interrogations.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The second key finding was that the vast majority of interrogators in our sample did not make use of multiple and varied methods to assess and aid understanding. Consistent with previous studies, the youth in this sample typically claimed to understand the rights with a "yes" answer, even though research has shown that youth tend to demonstrate a lack of understanding when explaining interrogation rights in their own words, have serious misconceptions about their interrogation rights, and simply cannot understand the complex information presented to them (e.g., Cooke & Philip, 1998;Fenner et al, 2002;Freedman et al, 2016;Shepherd et al, 1995); very rarely did interrogators in our sample attempt to verify the youth's understanding. With respect to seeking evidence of understanding, youth were asked to explain all four rights in their own words in less than 10% of interrogations, and youth were asked to explain at least one of the rights in their own words in just over a third of interrogations.…”
Section: Discussionsupporting
confidence: 82%
“…Interrogators in the current sample spoke to youth suspects at approximately 205 wpm when delivering the interrogation rights; a rate that exceeds what is acceptable for maximum comprehension. Research has shown that simplifying the youth waiver form (Eastwood et al, 2016) and providing simple explanations of the legal concepts leads to increased youth understanding (Eastwood and Snook, 2012; Freedman et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Yet interviewers typically do not verify or test suspects’ understanding of the caution (Snook et al, 2010; Sim and Lamb, 2018; Walsh and Bull, 2010, 2012). Explanations are needed to improve suspects’ comprehension of the caution (Eastwood and Snook, 2012; Eastwood et al, 2016; Snook et al, 2014). However, in various countries when officers or investigators do explain, they do so inconsistently (Snook et al, 2010; Walsh and Bull, 2011) or incorrectly (Walsh and Bull, 2010, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This means the young people who most likely will need to use these rights in practice are the ones who will be less likely to understand them. Despite this body of research, versions of the Cautions with simplified language produce only small effects on understanding (Freedman et al, 2014;Eastwood et al, 2016). However, studies using simplified versions of the Caution have typically assessed understanding only using recall, and so it is unclear what the impact of these versions would be on the other aspects of understanding.…”
Section: Reasons For Young People's Difficulties With Legal Rightsmentioning
confidence: 99%